ANALYZING KEY FACTORS THE GLAMPING VIOVIO BEACH BATAM BASED ON CUSTOMER PERSPECTIVE - Putra, Muhamad Zhabiyan Dwi; Ang, Jessica Friscilla (Jurnal Pariwisata PaRAMA : Panorama, Recreation, Accomodation, Merchandise, Accessbility, 2025)
The growing popularity of glamping, an upscale form of camping that blends luxury with nature, has had a significant impact on tourism trends worldwide. This study investigates the influence of the glamping trend on tourists' re-visit intentions to Viovio Beach in Batam, Indonesia. By employing a word cloud diagram analysis of reviews from TripAdvisor, this research identifies key factors that shape visitor experiences and preferences. The findings reveal that Viovio Beach is generally well-regarded for its natural beauty and amenities, though certain areas, such as infrastructure and facility maintenance, could be improved. The study highlights the importance of continuing to enhance the beach’s positive attributes while addressing potential shortcomings to increase tourist satisfaction and revisit rates